2019
DOI: 10.1016/j.cell.2019.07.035
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Packing Portal and Capsid-Associated Tegument Complexes in the Tumor Herpesvirus KSHV

Abstract: Graphical Abstract Highlights d Genome-packing portal and capsid-associated tegument complexes (CATCs) resolved d Partial and asymmetric CATC occupancy introduces structural variability d CATC binding introduces 120 counterclockwise rotation of triplex Ta on the capsid d Structure-based mutageneses reveal binding hotspot for antiviral development SUMMARYAssembly of Kaposi's sarcoma-associated herpesvirus (KSHV) begins at a bacteriophage-like portal complex that nucleates formation of an icosahedral capsid with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
110
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(125 citation statements)
references
References 69 publications
8
110
1
Order By: Relevance
“…Structural investigations of the herpesvirus portal have proven challenging due to the small size of this dodecamer, which accounts for less than 1% of the total mass of the capsid protein layer and the technical difficulties involved in resolving non-icosahedral components of such large icosahedral viruses (diameter is ∼1,250 Å). Efforts of many investigators over two decades have made to reconstruct the cryo-electron microscopy (cryo-EM) structure of herpesvirus portal vertex and more recently near-atomic structures of two herpesvirus (herpes simplex virus type 1 (HSV-1) and Kaposi's sarcoma-associated herpesvirus (KSHV)) portal vertices were reported (McElwee et al, 2018;Gong et al, 2019;Liu et al, 2019).…”
mentioning
confidence: 99%
“…Structural investigations of the herpesvirus portal have proven challenging due to the small size of this dodecamer, which accounts for less than 1% of the total mass of the capsid protein layer and the technical difficulties involved in resolving non-icosahedral components of such large icosahedral viruses (diameter is ∼1,250 Å). Efforts of many investigators over two decades have made to reconstruct the cryo-electron microscopy (cryo-EM) structure of herpesvirus portal vertex and more recently near-atomic structures of two herpesvirus (herpes simplex virus type 1 (HSV-1) and Kaposi's sarcoma-associated herpesvirus (KSHV)) portal vertices were reported (McElwee et al, 2018;Gong et al, 2019;Liu et al, 2019).…”
mentioning
confidence: 99%
“… 20 For example, while the human cytomegalovirus (HCMV) capsid contains the largest genome of 235-kb dsDNA and has both the pentons and hexons being secured by CMV-specific pp150 tegument protein, 15 , 21 the herpes simplex virus (HSV) and KSHV containing much smaller genomes of 150 kb and 165 kb, respectively, have only their pentons being secured by CATCs. 17 , 18 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…With the rapid advance of cryo-electron microscopy (cryoEM), the atomic structures of several herpesviruses, such as HCMV, HSV-1, HSV-2, and KSHV, 15 18 have been determined, and more recently, the in situ portal structures of HSV-1 and KSHV were also resolved by cryoEM. 22 , 23 In contrast to these great successes, the progress toward an atomic description of the EBV capsid has been hindered, likely by the difficulties of EBV virion sample preparation, and the highest-resolution reconstruction of the EBV capsid, which was determined 8 years ago, remains 20 Å. 24 Here, by using an optimized viral culture method modified from previous procedure 25 and cryoEM, we obtained high-resolution reconstructions of the EBV icosahedral capsid, dodecameric portal and CATC.…”
Section: Introductionmentioning
confidence: 99%
“…With the advance of cryo-electron microscopy (cryo-EM), the high-resolution structures of herpesvirus capsid (Yu et al, 2017;Wang et al, 2018;Yuan et al, 2018) and the unique portal-vertex (Gong et al, 2019;Liu et al, 2019) of the infectious virion have been determined recently. These results showed that the structures of the herpesvirus major capsid protein and the portal, as well as the interactions among them closely resemble that of the tailed DNA bacteriophage, indicating the herpesvirus shares a common mechanism of the capsid assembly and genome package with the bacteriophage (Yu et al, 2017;Wang et al, 2018;Yuan et al, 2018;Gong et al, 2019;Liu et al, 2019;Chen et al, 2020). Although these achievements greatly advanced our understanding the structures and functions of herpesvirus capsid and portal, there are still questions regarding the herpesvirus capsid assembly and genome package: 1) what's the working mechanism of the herpesvirus terminase?…”
mentioning
confidence: 99%
“…The molecular rearrangement between the ATPase domain and nuclease domain in the terminase caused by ligand binding, as well as the big central channel of the hexameric motor (39 Å in diameter) observed by the researchers favor the previously proposed revolution model of viral DNA translocation and cleavage. Considering the fact that a majority region in the viral portal turret (the putative site for terminase complex anchoring) in mature capsids were determined to be disordered (Gong et al, 2019;Liu et al, 2019;Nan Wang, 2020), we cannot even exclude the possibility that the DNA packaging motors have the ability to transform between pentamer and hexamer during DNA packaging. It would be fabulous to see the in situ structure of the viral terminase, while it is indeed too challenging since that tremendous efforts of many investigators over two decades failed.…”
mentioning
confidence: 99%